Characterization of obstetric patients with sepsis identified by two diagnostic scales at a fourth‐level clinic in Colombia. Issue 1 (23rd July 2018) - Escobar, María F.; Nasner, Daniela; Hurtado, Carlos F.; Fernández, Paula A.; Echavarria, Maria P.
Abstract: Objective: To compare the characterization of an obstetric population diagnosed with sepsis using systemic inflammatory response syndrome (SIRS) criteria and sepsis‐related organ failure assessment (SOFA). Methods: The present retrospective observational descriptive study was conducted at a fourth‐level clinic in Colombia among pregnant women who met the inclusion criteria (two SIRS criteria plus infection) between January 1, 2015, and December 31, 2016. Patients with systemic compromise were admitted to the high‐complexity obstetric unit (HCOU), whereas those with multiorgan dysfunction were admitted to the intensive care unit (ICU). The SIRS scale was deemed positive if all four criteria were met. A SOFA score of at least 2 was considered a positive result. Results: The study included 688 patients. The SIRS test at admission was positive among 431 patients (62.6%); 279 (64.7%) in the HCOU group and 152 (35.2%) in the ICU group. The SOFA test at admission was positive in 69 (38.5%) of 179 patients with complete data. The concordance—measured using the κ statistic—between SIRS and SOFA was low (0.016). Conclusion: Using the SIRS scale could promote early sepsis management by identifying patients who require admission to the HCOU or ICU; however, low concordance between the SIRS and SOFA results suggested a need to create diagnostic scales specifically for the obstetric population. Abstract : The two scales used to diagnosis sepsis showed low concordance; therefore, an urgent need exists to standardize diagnostic criteria among obstetric patients in Colombia. This article includes a Spanish translation of the Abstract, available in the Supporting Information section.